Pulmonary tuberculosis induces a systemic hypercoagulable state. Issue 4 (April 2015) - Kager, Liesbeth M.; Blok, Dana C.; Lede, Ivar O.; Rahman, Wahid; Afroz, Rumana; Bresser, Paul; van der Zee, Jaring S.; Ghose, Aniruddha; Visser, Caroline E.; de Jong, Menno D.; Tanck, Michael W.; Zahed, Abu Shahed M.; et al.
Summary: Objectives: Human tuberculosis (TB) remains an important cause of death globally. Bangladesh is one of the most affected countries. We aimed to investigate the impact of pulmonary TB on pro- and anticoagulant mechanisms. Methods: This prospective study was conducted in Chittagong, Bangladesh. We performed an in-depth analysis of coagulation activation and inhibition in plasma obtained from 64 patients with primary lung TB and 11 patients with recurrent lung TB and compared these with 37 healthy controls. Additionally, in nine patients coagulation activation was studied in bronchoalveolar lavage fluid (BALF) harvested from the site of infection and compared with BALF from a contralateral unaffected lung subsegment. Results: Relative to uninfected controls, primary and recurrent TB were associated with a systemic net procoagulant state, as indicated by enhanced activation of coagulation (elevated plasma levels of thrombin-antithrombin complexes, D-dimer and fibrinogen) together with impaired anticoagulant mechanisms (reduced plasma levels of antithrombin, protein C activity, free protein S, and protein C inhibitor). Activation of coagulation did not correlate with plasma concentrations of established TB biomarkers. Coagulation activation could not be detected at the primary site of infection in a subset of TB patients. Conclusions: Pulmonary TB is associated with a systemic hypercoagulable state. Highlights: Tuberculosis is one of the most common infectious diseases world-wide. Besides pro-inflammatory responses, severe infections also involve haemostatic mechanisms. During infection procoagulant factors are activated while anticoagulant mechanisms are suppressed. Data on activation of the coagulation system during tuberculosis are highly limited. We analyzed systemic coagulation and anticoagulant pathways in lung tuberculosis patients. We show that pulmonary tuberculosis is associated with a systemic hypercoagulable state.